The level of environmental behavior among kindergarten teachers (A field study in the city of Latakia) - حسن, آلاء; بشرى شريبه, (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The aim of the research is to identify the level of environmental behavior among kindergarten teachers in the city of Latakia, and to identify the differences in their level of environmental behavior according to the variables (academic qualification and years of experience).To achieve the objectives of the research, the researcher followed the descriptive approach and used the Shan scale for environmental awareness in its third form, which includes among its dimensions environmental what measures inter-personal behavior (Shrebah et al, 2016), as it was codified in a way that is appropriate to the Syrian environment. It was applied to a sample of kindergarten teachers, numbering (49) teachers and the sample was drawn in a simple random method. The results showed that the level of environmental behavior among kindergarten teachers in the city of latakia was high, and the results showed that there were no differences in environmental behavior among kindergarten teachers according to the variables of academic qualification and years of experience.